Enhancing NO2 sensing performance and stability: low-crystallinity conjugated polymers with localized aggregates via ethylene glycol pendants - An, Jung-Won; Jang, Ho Won; Jang, Ji-Soo; Lee, Junwoo (Royal Society of Chemistry, 2025)
Conjugated polymers are of utmost importance for the detection of harmful gas phase chemicals. However, the development of highly sensitive polymers remains a challenge due to the trade-off between gas diffusion and crystallinity. In this study, we report a solution to this issue based on low crystallinity with localized aggregates. This designed morphology mediated by substitution with ethylene glycol pendant groups not only enhances electrical conductivity but also simultaneously improves the diffusion and affinity between the polymer matrix and nitrogen dioxide. Moreover, the promoted amorphous nature suppressed morphological degradation, thus offering highly sensitive chemiresistors with enhanced stability against elevated temperature.